Candida albicans effects the tissue factor activity of blood cells in Type II Diabetes Mellitus - (:unkn) unknown (MARMARA UNIV, FAC PHARMACY, 2015)
Disorders of hemostatic mechanism play a role in the development of diabetic complications and cardiovascular events. C. albicans infection is frequently found in diabetic individuals compared to nondiabetic individuals. In this study, the in vitro effect of Candida albicans on the tissue factor activity of the PMNS, MNS and platelet cells, that were isolated from the blood samples of healthy and diabetic individuals, was determined. The isolated blood cells were counted after the viability test has been checked. C. albicans suspension was added to one part of the cells. An equal volume phosphate buffer was added to other part of the cells instead of C. albicans suspension. Tissue factor activity of all blood cells was determined by the method of Quick. Tissue factor activity of these cells was found to be significantly changed in the presence of C. albicans. The presence of diabetes was also significantly changed tissue factor activity of the PMNs, MNs and platelet cells when compared to the healthy individuals. The findings of this study will contribute to the treatment of diabetic patients with or without candida infection in terms of tissue factor activity.
Keywords: Tissue factor activity; diabetes; Candida albicans; leukocyte; platelet; FACTOR PROCOAGULANT ACTIVITY; EXPRESSION; INSULIN; STANDARDIZATION; COLONIZATION; HEMOSTASIS; INHIBITION